Cover Picture: Tailoring Preferential Orientation in BaTiO3‐based Thin Films from Aqueous Chemical Solution Deposition (Chem. Methods 2/2022). Issue 2 (1st February 2022) - Bakken, Kristine; Blichfeld, Anders B.; Nylund, Inger‐Emma; Chernyshov, Dmitry; Glaum, Julia; Grande, Tor; Einarsrud, Mari‐Ann
Abstract : The Front Cover shows our in‐situ X‐ray diffraction setup for analysing the crystallization process in oxide thin films made by chemical solution deposition. By adjusting the process parameters, the nucleation and growth conditions are changed and the degree of preferred orientation and epitaxi in the oxide films can be tailored. This change is illustrated by the change in microstructure of the polycrystalline films with random orientation (left) towards highly oriented cube‐on‐cube grown films (right) where the film unit cell follows that of the substrate. This effect can be observed experimentally by the appearance of spot reflection instead of full diffraction rings on the detector. More information can be found in the Full Paper by Kristine Bakken et al .